Susceptibility-Weighted Imaging Findings in Aspartylglucosaminuria - Tokola, A.; Laine, M.; Tikkanen, R.; Autti, T. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Aspartylglucosaminuria is a rare lysosomal storage disorder that causes slowly progressive, childhood-onset intellectual disability and motor deterioration. Previous studies have shown, for example, hypointensity in the thalami in patients with aspartylglucosaminuria on T2WI, especially in the pulvinar nuclei. Susceptibility-weighted imaging is a neuroimaging technique that uses tissue magnetic susceptibility to generate contrast and is able to visualize iron and other mineral deposits in the brain. SWI findings in aspartylglucosaminuria have not been reported previously.MATERIALS AND METHODS: Twenty-one patients with aspartylglucosaminuria (10 girls; 7.4–15.0 years of age) underwent 3T MR imaging. The protocol included an SWI sequence, and the images were visually evaluated. Thirteen patients (6 girls, 7.4–15.0 years of age) had good-quality SWI. Eight patients had motion artifacts and were excluded from the visual analysis. Thirteen healthy children (8 girls, 7.3–14.1 years of age) were imaged as controls.RESULTS: We found a considerably uniform distribution of decreased signal intensity in SWI in the thalamic nuclei in 13 patients with aspartylglucosaminuria. The most evident hypointensity was found in the pulvinar nuclei. Patchy hypointensities were also found especially in the medial and anterior thalamic nuclei. Moreover, some hypointensity was noted in globi pallidi and substantia nigra in older patients. The filtered-phase images indicated accumulation of paramagnetic compounds in these areas. No abnormal findings were seen in the SWI of the healthy controls.CONCLUSIONS: SWI indicates accumulation of paramagnetic compounds in the thalamic nuclei in patients with aspartylglucosaminuria. The finding may raise the suspicion of this rare disease in clinical practice.AGAaspartylglucosaminidaseAGUaspartylglucosaminuriaSIsignal intensity